Development of AI-Based Website to improve the competence of teaching module for Trainees - Novi Kurniasih; Akhmad Arif Musadad; Leo Agung Sutimin (Dinasti Publisher, 2025)
This research aims to develop an artificial intelligence (AI)-based website specifically designed for the preparation of teaching modules for e-Guru.id trainees. With the increasing need for quality and relevant teaching materials, the development of this AI-based website is expected to facilitate educators in creating effective and innovative teaching modules. This research used the Borg n Gall development which was simplified by Sukmadinata 2013. Expert validation was conducted to assess the feasibility and effectiveness of the teaching modules produced, focusing on pedagogical and technical aspects. The results showed that this website not only increased efficiency in the preparation of teaching modules, but also provided a more interactive and interesting learning experience for trainees. Based on the validation results, the Artificial Intelligence-based website development was declared valid based on the assessment of media experts with an average of 88% and the assessment of material experts with an average score of 91%. In addition, the module is declared in accordance with the Learning and language rules to get an average score of 79% so that it is feasible to use in training in making teaching modules for trainees at e-Guru.id. These findings are expected to make a positive contribution to the development of teacher professionalism and improving the quality of education in the digital era.